2012
DOI: 10.1038/embor.2013.5
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted role of mTORC1 in the control of lipid metabolism

Abstract: The mechanistic target of rapamycin is a protein kinase that, as part of the mechanistic target of rapamycin complex 1 (mTORC1), senses both local nutrients and, through insulin signalling, systemic nutri ents to control a myriad of cellular processes. Although roles for mTORC1 in promoting protein synthesis and inhibiting autophagy in response to nutrients have been well established, it is emerging as a central regulator of lipid homeostasis. Here, we discuss the growing genetic and pharmacological evidence d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
190
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(198 citation statements)
references
References 93 publications
(140 reference statements)
6
190
0
2
Order By: Relevance
“…The emerging role of mTORC1 in lipid homeostasis has captured the attention of many labs involved in the metabolic research (42,43). In particular, we have recently shown that mTORC1 mediates the effect of insulin on lipolysis in mammalian adipocytes by suppressing the expression of the rate-limiting lipase, ATGL, at the level of transcription (6).…”
Section: Discussionmentioning
confidence: 99%
“…The emerging role of mTORC1 in lipid homeostasis has captured the attention of many labs involved in the metabolic research (42,43). In particular, we have recently shown that mTORC1 mediates the effect of insulin on lipolysis in mammalian adipocytes by suppressing the expression of the rate-limiting lipase, ATGL, at the level of transcription (6).…”
Section: Discussionmentioning
confidence: 99%
“…S11B). Next to the transcriptional program of the adipogenesis, mTORC1 controls the balance between lipogenesis and lipolysis in adipocytes (46). Essential proteins for the LD accumulation and thus, the initiation of lipid storage and lipogenesis are substrates of the mTORC1 as, for example, lipin-1 (47).…”
Section: Discussionmentioning
confidence: 99%
“…Membrane lipid homeostasis regulated by ORP5 and other lipid transfer proteins has an impact on mTORC1, which itself is a key regulator of lipid metabolism, as well as protein synthesis and cell proliferation (4). Notably, ORP5 appears to be a phosphatidylserine transporter (14) and has been shown to deliver phosphatidylserine from the ER to the plasma membrane and mitochondria (15)(16)(17).…”
Section: Orp5 Depletion Impairs the Localization Of Mtor To Lysosomesmentioning
confidence: 99%
“…In this regard, activated mTORC1 phosphorylates and activates its major downstream effector ribosomal protein S6 kinase (S6K). Once activated, S6K phosphorylates the ribosomal S6 protein to control fundamental cellular processes including protein synthesis, lipid metabolism, and cell proliferation (3,4).…”
Section: Introductionmentioning
confidence: 99%